2011
DOI: 10.1007/s00592-011-0347-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of bone resorption markers are decreased in patients with type 2 diabetes

Abstract: Previous studies of bone turnover markers in diabetes are limited, and the results are conflicting. Our aim was to evaluate differences in bone turnover markers and i-PTH between T2DM and non-diabetes subjects. Cross-sectional study including 133 subjects (78 T2DM, 55 without diabetes). BMD were measured by dual X-ray absorptiometry. Bone turnover markers were determined in serum. Serum levels of bone resorption markers (CTX and TRAP5b) were lower in T2DM compared with non-diabetes subjects. There were no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 22 publications
6
52
3
1
Order By: Relevance
“…Previous studies in type 2 diabetes have shown the decreased levels of bone turnover markers in type 2 diabetic patients compared to nondiabetic control subjects [15,16]. And some studies indicated that improved glycemic control in diabetic patients resulted in change in bone turnover markers [17][18][19], which is not found in the present study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Previous studies in type 2 diabetes have shown the decreased levels of bone turnover markers in type 2 diabetic patients compared to nondiabetic control subjects [15,16]. And some studies indicated that improved glycemic control in diabetic patients resulted in change in bone turnover markers [17][18][19], which is not found in the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…It is still not clear what factors induce these controversial results. What should be addressed is that bone turnover markers levels were shown to be correlated with diabetes duration [15]. The subjects in our study are patients with newly diagnosed type 2 diabetes and were treated with monotherapy of hypoglycemic agents for 6 months, who are quite different with those patients enrolled in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher levels of sclerostin correlate positively with duration of T2DM and levels of glycated hemoglobin, while negatively with levels of bone turnover markers. Another study from the same group reported decreased levels of both serum bone resorption markers (CTX and TRAPc) and intact PTH in patients with T2DM as compared to nondiabetic control (18). Decrease in levels of bone resorption markers and PTH correlated with increased BMD and duration of disease.…”
Section: Skeletal Status and Fracture Risk In T2dmmentioning
confidence: 87%
“…As a result, insulin increases bone turnover and production of undercarboxylated osteocalcin, which in endocrine fashion regulates insulin release from β-cells in pancreas and production of adiponectin in fat tissue (13)(14)(15)(16). Although it is not clear whether this regulatory circuit is affected in diabetes, several studies suggest that patients with T2DM have decreased bone turnover (17)(18)(19). If so, it would result in the decrease in osteocalcin production, especially its undercarboxylated form, which would lead to the attenuation of signaling responsible for increasing of insulin release from the pancreas and increasing fat sensitivity to insulin.…”
Section: Bone As An Integral Part Of Energy Metabolism Systemmentioning
confidence: 99%
“…This suggests poorer structural integrity of bone may play a role in the increased rate of fragility fractures in patients with T2DM. This is thought to be linked with reduced bone activity, as evidenced by lower levels of biochemical measures of bone turnover and parathormone in patients with T2DM [16]. There are several proposed mechanisms for this reduced bone activity.…”
Section: Mechanismsmentioning
confidence: 99%